Antihistamines suppress upregulation of histidine decarboxylase gene expression with potencies different from their binding affinities for histamine H1 receptor in toluene 2,4-diisocyanate-sensitized rats - Hiroyuki Mizuguchi; Asish K. Das; Kazutaka Maeyama; Shrabanti Dev; Masum Shahriar; Yoshiaki Kitamura; Noriaki Takeda; Hiroyuki Fukui (Elsevier, 2016)
Antihistamines inhibit histamine signaling by blocking histamine H1 receptor (H1R) or suppressing H1R signaling as inverse agonists. The H1R gene is upregulated in patients with pollinosis, and its expression level is correlated with the severity of nasal symptoms. Here, we show that antihistamine suppressed upregulation of histidine decarboxylase (HDC) mRNA expression in patients with pollinosis, and its expression level was correlated with that of H1R mRNA. Certain antihistamines, including mepyramine and diphenhydramine, suppress toluene-2,4-diisocyanate (TDI)-induced upregulation of HDC gene expression and increase HDC activity in TDI-sensitized rats. However, d-chlorpheniramine did not demonstrate any effect. The potencies of antihistamine suppressive effects on HDC mRNA elevation were different from their H1R receptor binding affinities. In TDI-sensitized rats, the potencies of antihistamine inhibitory effects on sneezing in the early phase were related to H1R binding. In contrast, the potencies of their inhibitory effects on sneezing in the late phase were correlated with those of suppressive effects on HDC mRNA elevation. Data suggest that in addition to the antihistaminic and inverse agonistic activities, certain antihistamines possess additional properties unrelated to receptor binding and alleviate nasal symptoms in the late phase by inhibiting synthesis and release of histamine by suppressing HDC gene transcription.